(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The aim of research was to analyse and explain the variation of accumulating associations of 13 chemical elements Ag, B, Ba, Co, Cr, Cu, Mn, Mo, Ni, Pb, Sn, V, Zn in topsoil of the oldest part of Vilnius. These elements characterise soil quality and are included in the check list of hygienic norm HN 60- 2004 of Lithuania. According to adjusted accumulating associations ordinary and unusual associations have been distinguished and distribution of the types or unusual associations has been analysed. They are often near present or former industrial sites, railway or streets with intensive traffic.